2011
DOI: 10.1007/s10870-011-0190-8
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure and Cytotoxicity of Centrosymmetric Copper(II) Complex Derived from S-methyldithiocarbazate with Isatin

Abstract: Copper(II) complex of S-methyldithiocarbazate with isatin has been prepared and screened for their cytotoxic activities against MCF-7 (Human non-metastatic mammary gland adenocarcinoma cell line) and MDA-MB-231 (Human metastatic mammary gland adenocarcinoma cell line). The compound crystallized in an orthorhombic crystal system with a space group C 2cb and was found to be selectively active against MCF-7 cell line (Human non-metastatic mammary gland adenocarcinoma cell line with an IC50 value 0.45 μg/mL. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…N1 chelating angle of 84.41 (5) . It is worth of note that copper(II) complexes with similar dithiocarbazate ligands assume a distorted tetrahedral configuration as well (Tarafder, et al, 2008;Manan, et al, 2011). In these derivatives the coordination distances are close comparable to those here reported.…”
Section: Structural Commentarysupporting
confidence: 82%
“…N1 chelating angle of 84.41 (5) . It is worth of note that copper(II) complexes with similar dithiocarbazate ligands assume a distorted tetrahedral configuration as well (Tarafder, et al, 2008;Manan, et al, 2011). In these derivatives the coordination distances are close comparable to those here reported.…”
Section: Structural Commentarysupporting
confidence: 82%
“…However, in CuSBHD molecules are linked by a combination of C-H…S and C-H…π (phenyl) interactions. Geometric parameters characterising the intermolecular interactions operating in the crystal structure of CuSBHD: C4-H4a...S4 i = 2.83 Å, C4...S4 i = 3.7647(16) Å, and angle at H4a = 158º for i: -x, -½+y, -½z; C4-H4b...S3 ii = 2.84 Å, C4...S3 ii = 3.6946(19) Å, and angle at H4b = 145º for ii: -x, 1-y,z; C18-H18...S4 iii = 2.86 Å, C18...S4 iii = 3.6811(17) Å, and angle at H18 = 145º for iii: x, 1½-y, -½+z; C3-H3a...Cg(C17-C22) i = 2.89 Å, C3...Cg(C17-C22) i = 3.6538(17) Å, and angle at H3a = 135º.The observed four-coordinate structures described here for CuSBHD and CuSMHD, with the dianions in the iminothiolate form, is consistent with literature precedents[15,16,[48][49][50][51].…”
supporting
confidence: 90%
“…The sulphur-nitrogen chelating agents derived from S-alkyl/aryl esters of dithiocarbazic acid have been extensively investigated in recent years for their potential anticancer [7,8], antibacterial [9], antiamoebic [10], anti-Trypanosoma cruzi [11] and anti-Mycobacterium tuberculosis [12] activities. Considerable attention continues to be given to these and related Schiff base ligands [13][14][15][16], since their properties can be modulated by introducing different substituents through condensation of various S-substituted dithiocarbazate esters with a wide array of aldehydes and ketones. In many cases, the biological properties of dithiocarbazate derivatives have been shown to be widely different although there may be only slight variation in their molecular structures [8].…”
Section: Introductionmentioning
confidence: 99%
“…The Re-N (2.200(2) Å ), Re-S (2.4669(7) Å ) and Re-S 0 (2.5565(7) Å ) distances do not differ significantly from those determined for Re complex studied by Carballo et al (2002). As in several related complexes (Beshir et al 2008;Ali et al 2008;Manan et al 2011b), a Z-configuration was observed at N2-C12, imposed by the N1-S1 chelation to the rhenium. The N1-Re-S1 bond angle was determined to be only 79.13(6)°.…”
Section: Ir Spectroscopymentioning
confidence: 60%
“…Apart from their significant bioactivities, their Lewis base character could give rise to various coordination modes and interesting modulation of bioactivity (Farrer and Sadler 2011). For instance, the Schiff base formed from isatin and Smethyl-dithiocarbazate can act either as a tridentate ONS ligand in six-coordinate distorted octahedral NiL 2 or as a bidentate NS chelator in four-coordinate distorted tetrahedral ZnL 2 (Ali et al 2008;Manan et al 2011b). Another example involves quinoline with 4(N,N)-dimethylthiosemicarbazone which produced a novel water-soluble sulphur-bridged binuclear copper(II) complex (Senthil Raja et al 2011).…”
Section: Introductionmentioning
confidence: 99%